The Role of Thioredoxin/Peroxiredoxin in the β-Cell Defense Against Oxidative Damage - Stancill, Jennifer S.; Corbett, John A. (Frontiers in Endocrinology, 2021)
Oxidative stress is hypothesized to play a role in pancreatic beta-cell damage, potentially contributing to beta-cell dysfunction and death in both type 1 and type 2 diabetes. Oxidative stress arises when naturally occurring reactive oxygen species (ROS) are produced at levels that overwhelm the antioxidant capacity of the cell. ROS, including superoxide and hydrogen peroxide, are primarily produced by electron leak during mitochondrial oxidative metabolism. Additionally, peroxynitrite, an oxidant generated by the reaction of superoxide and nitric oxide, may also cause beta-cell damage during autoimmune destruction of these cells. Beta-cells are thought to be susceptible to oxidative damage based on reports that they express low levels of antioxidant enzymes compared to other tissues. Furthermore, markers of oxidative damage are observed in islets from diabetic rodent models and human patients. However, recent studies have demonstrated high expression of various isoforms of peroxiredoxins, thioredoxin, and thioredoxin reductase in beta-cells and have provided experimental evidence supporting a role for these enzymes in promoting beta-cell function and survival in response to a variety of oxidative stressors. This mini-review will focus on the mechanism by which thioredoxins and peroxiredoxins detoxify ROS and on the protective roles of these enzymes in beta-cells. Additionally, we speculate about the role of this antioxidant system in promoting insulin secretion.